Sudden pulmonary edema induced by phenylephrine misuse: a case report - Xie, Qing; Tian, Dong-Dong; Lu, Jia (Vojnosanitetski pregled, 2026)
Introduction. Phenylephrine, a widely used vasoactive drug in clinical practice, may lead to severe cardiovascular complications when misused. Among these complications, sudden pulmonary edema, though rare, warrants the attention of clinicians. The given case report presents a sudden pulmonary edema caused by the misuse of phenylephrine. Case report. A female patient aged 68-years undergoing radical mastectomy for left breast cancer developed severe hypertension and hypoxemia 40 min into the procedure. The patient’s medical history included meningioma but no other significant comorbidities. A diagnosis of sudden (acute) pulmonary edema was made. The patient received prompt treatment, including strict perioperative blood pressure control, lung protective ventilation, glucocorticoids, diuretics, coronary-dilation and cardiotonic drugs, postoperative oxygen therapy, and continuous vital sign monitoring. Investigation revealed that phenylephrine had been mistakenly administered intravenously instead of dexamethasone. She recovered and was discharged one week postoperatively. Conclusion. This case highlights the risks associated with the inadvertent administration of a high dose of phenylephrine, leading to sudden pulmonary edema. It underscores the importance of vigilance among anesthesiologists, prompt management of complications, and strategies to prevent errors, including enhanced education for resident anesthesiologists, measures to address practitioner fatigue, and improved drug packaging to minimize look-alike errors.
Keywords: anesthesia, intravenous; anesthesiologists; intensive care units; medical errors; phenylephrine; pulmonary edema.